Costume and Sustainability: From Past Practice to Future Strategies for an Ecological Costume Praxis - Pantouvaki , Sofia; Fossheim, Ingvill; Suurla, Susanna (Peripeti, 2022)
What can we learn from past traditions and what sustainability practices are currently employed in the field of costume? Moving towards a more ecological costume creation, there is an increasing need to address the responsibility of the costume practitioners through the lifecycle of costume from design to production. This article provides an overview of current sustainable costume practices and suggests that it is timely to rethink costume praxis from an ecologically responsible perspective. The article addresses the necessity of embedding ecological equity into all aspects of costume creation and proposes that a resilient ecosystem of costume practice can be envisioned within professional institutions, as well as the individual costume designer.